Isolation and characterization of bacterial strains with the ability to utilize high concentrations of levulinic acid, a platform chemical from inedible biomass. Issue 9 (2nd September 2015) - Habe, Hiroshi; Sato, Shun; Morita, Tomotake; Fukuoka, Tokuma; Kirimura, Kohtaro; Kitamoto, Dai
Abstract: Nineteen levulinic acid (LA)-utilizing bacteria were isolated from environmental samples. Following examination of the use of 80 g/L LA by some isolated strains, Brevibacterium epidermidis LA39–2 consumed 62.6 g/L LA following 8 days incubation. The strain also utilized both 90 and 100 g/L LA, with consumption ratio of 84.3 and 53.3%, respectively, after 10 days incubation.